Molecular Layer Deposition of Alucone Thin Film on LiCoO2 to Enable High Voltage Operation - Lidor-Shalev O.; Leifer N.; Ejgenberg M.; Aviv H.; Perelshtein I.; Goobes G.; Noked M.; Rosy (My University, 2025)
Extracting the theoretically high capacity of LiCoO2 (LCO) is desirable for enhancing the energy density of currently used lithium-ion batteries (LIBs) for portable devices. The bottleneck for exhibiting the high capacity is associated with the limited cut-off positive voltages beyond which degradation of electrode/electrolyte takes place. In this work, we apply hybrid organic-inorganic alucone thin film grown directly on LCO by a molecular layer deposition (MLD) method, using sequential exposure to Al-based and organic-based precursors. The alucone thin films enabled the high voltage operation of the LCO cathode (>4.5 V), acting as a protection layer. Electrochemical studies proved that alucone coated LCO show enhanced electrochemical performances with improved cycling stability and enhanced specific capacity, relative to uncoated LCO. Amongst the studied films, 10 nm ethylene glycol/Al coated LCO have shown the best results. © 2021 Wiley-VCH GmbH